A Method to Prepare a Descemet's Stripping Automated Endothelial Keratoplasty (DSAEK) Graft Using Donor Corneas With Narrow Scleral Rims: A Case Report - Lin, Tzu-Yu; Hwang, Yih-Shiou; Ma, David Hui-Kang (Medicine (Baltimore), 2015)
Donor corneas with narrow scleral rims are often disqualified for Descemet's Stripping Automated Endothelial Keratoplasty (DSAEK), mainly because of fluid leak and low pressure when they are mounted onto an artificial anterior chamber (AAC). This report describes a novel method to tight-lock a donor cornea with a narrow scleral rim so that microkeratome cutting is possible, allowing a DSAEK procedure to be completed. A 50-year-old male suffering from Epstein-Barr virus (EBV) endotheliitis with resulting corneal edema in his left eye was the subject of this study. His best corrected visual acuity (BCVA) was 20/600. The patient underwent a DSAEK procedure; however, the microkeratome cutting of the donor cornea initially failed due to its narrow scleral rim, which caused the balance salt solution (BSS) to leak out of the AAC. A doughnut-shaped cushion was made from a surgical glove, which enabled a tight lock of the cornea to the AAC, enabling the chamber pressure to be raised and the microkeratome cutting to be completed. A subsequent DSAEK procedure was performed uneventfully. Postoperatively, the patient received oral valganciclovir 450 mg b.i.d. to prevent EBV recurrence. The graft remained clear at 5 months post-op, and the patient's BCVA improved to 6/7.5. His endothelial count was 1830, which was ∼ 79% of the original value. Inserting a self-made cushion can enable donor corneas with narrow scleral rims to be used in DSAEK procedures and avoids unwanted switching from endothelial keratoplasty to penetrating keratoplasty (PKP).